Application of GSA/GLUE methods to evaluate the representation of suspended sediment transport during flash floods in a rainfall-runoff model. Issue 5 (2022) - Hosseinzadeh, A.; Roux, H.; Cassan, L.; Douinot, A.
Abstract: This study looks at the impact of different parameters involved in the simulation of suspended sediment transport during flash flood on the performances of a distributed event-based soil erosion model. The results of GSA/GLUE methodologies implemented on three flash flood events show the model sensitivity to two parameters: the coefficient of soil sensitivity to shear erosion and the median diameter of sediment particles. The need to take into account the spatial variability of this soil sensitivity to shear erosion and therefore the location of potential sources of sediment is also stressed.